Development of a flipbook-based Javanese language teaching e-module to improve student learning outcomes - Indah Yuliarti; Triyo Supriyatno; Mohamad Zubad Nurul Yaqin (Research and Development in Education)
This research produces teaching material products in the form of electronic modules (e-modules) in class IV. The focus of the research discussed in this study is to: (1) Know the design of e-module development products to improve learning outcomes for class IV Javanese language subjects, (2) Find out the validity of e-modules to improve learning outcomes for class IV Javanese language subjects in the city Malang, and (3) Knowing the effectiveness of learning outcomes for class IV Javanese language subjects. This research uses the Research and Development (R&D) research method, referring to the ADDIE development model with stages including Analysis, Design, Development, Implementation and Evaluation. The result of this research is a Javanese e-module consisting of 33 pages. This e-module has validity from design experts of 85%, material experts of 85% and language experts of 93%. The results of the field test on the use of e-modules taken from the results of the fourth grade student questionnaire were 86.66%. Meanwhile, testing the effectiveness of the Javanese e-module on the learning outcomes of class IV students showed positive results. In terms of learning material, the results before using the e-module were 67.19 in the pre-test and increased after using the e-module in the post-test results to 81.19. The development of this e-module will later be useful for learning Javanese at primary level schools/madrasas, which of course this development can continue to be carried out to improve students' abilities and also teachers' abilities in terms of developing teaching materials.